2015
DOI: 10.5539/gjhs.v7n4p136
|View full text |Cite
|
Sign up to set email alerts
|

Computer Literacy Among Students of Zahedan University of Medical Sciences

Abstract: Introduction:The need for medical students to be computer literate is vital. With the rapid integration of information technology (IT) in the health care field, equipping students of medical universities withcomputer competencies to effectively use are needed. The purpose of this study was to assess computer literacy (CL) needs of medical sciences students.Methods:This is descriptive-analytic. The population of the study comprised all students at Zahedan University of Medical Sciences. 385 students from allsch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 5 publications
2
10
0
Order By: Relevance
“…This could indicate that Web browsing is a common skill among people who use computer technology. This result is consistent with those of previous studies that found Web browsing is on top priority when searching for information [ 11 , 12 ]. The results of the tutors’ assessments of the students further complemented these findings and confirmed the competency of most of the students (average grade=85%) in using computer programs (Microsoft Word, Excel, and PowerPoint).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This could indicate that Web browsing is a common skill among people who use computer technology. This result is consistent with those of previous studies that found Web browsing is on top priority when searching for information [ 11 , 12 ]. The results of the tutors’ assessments of the students further complemented these findings and confirmed the competency of most of the students (average grade=85%) in using computer programs (Microsoft Word, Excel, and PowerPoint).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, countries in the Middle East, such as Egypt, Jordan, and Saudi Arabia, have implemented different ICT tools, which have improved the students’ leaning experience [ 5 - 8 ]. In Iran, the impact of digital technologies applications on education has been studied [ 9 , 10 ], with particular attention on ICT literacy of medical students [ 11 , 12 ]. In Kuwait, research studies at Kuwait University found into information literacy and Internet use among students [ 13 ] and effectiveness of e-learning on learning environment [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite an upbringing in a digitized world, many students still lack some basic computing skills [29,30]. Recent surveys in different countries have also declared that biomedical sciences students' IL was unsatisfactory [31,32,33]. IL skills have become a necessity and an integral part of preparing tomorrow's doctors to be sufficiently competent to use informatics resources effectively and efficiently for the best practice of biomedical sciences [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Authors such as Adeleke and Emeahara (2016) and Robabi and Arbabisarjou (2015) have suggested that there is a causal relationship between computer literacy and the use of e-resources -that the more computer literate the students, the larger the increase in the use of e-resources. The problem of computer literacy at UNIZULU negatively affects the implementation and effective use of the E-learning Management System (ELMS), Moodle, which is used by the university.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%